2002
DOI: 10.1007/s774-002-8445-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of trace minerals in the pathogenesis of postmenopausal osteoporosis and a new effect of calcitonin

Abstract: The physiologic role of calcitonin in mineral and bone homeostasis is not very well understood. Very few longitudinal studies have reported the effects of calcitonin therapy on trace minerals in postmenopausal osteoporosis despite the documented involvement of trace minerals in normal skeletal metabolism. Several trace minerals, particularly magnesium (Mg) and zinc (Zn), essential for organic bone matrix synthesis have been known for at least three decades. The present study was designed to determine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 18 publications
0
38
0
1
Order By: Relevance
“…Similar to our study, Reginster et al [29] reported no significant difference in Cu and Zn plasma levels between postmenopausal women with osteoporosis and the non-osteoporotic control subjects. In contrast, several studies found that serum Zn and Cu levels were lower among patients with postmenopausal osteoporosis than with the controls [30,31]. p<0.05 was considered to be statistically significant Previously, it has been reported that there is an association between Zn deficiency and many kinds of skeletal abnormalities in fetal and postnatal development [32].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Reginster et al [29] reported no significant difference in Cu and Zn plasma levels between postmenopausal women with osteoporosis and the non-osteoporotic control subjects. In contrast, several studies found that serum Zn and Cu levels were lower among patients with postmenopausal osteoporosis than with the controls [30,31]. p<0.05 was considered to be statistically significant Previously, it has been reported that there is an association between Zn deficiency and many kinds of skeletal abnormalities in fetal and postnatal development [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the levels of copper have been shown by Gür et al [1], to be significantly lower in the serum of postmenopausal, as opposed to pre-menopausal, women. Similarly, Lowe et al [2] have shown that copper deficiency increases the rate of bone loss in postmenopausal women and these authors discussed the potential therapeutic value of copper in the amelioration of osteoporosis.…”
Section: Introductionmentioning
confidence: 91%
“…The participation of trace minerals in normal development and maintenance of the skeleton is related to their catalytic functions in organic bone matrix synthesis [24] . Calcium, a major component of bone matrix, has received considerable attention in the prevention and treatment of bone loss.…”
Section: Discussionmentioning
confidence: 99%